A distinct gradient of fouling occurs across shells of rare under-boulder chitons. (2nd January 2018) - Liversage, Kiran
ABSTRACT: It is recognised that more research is needed on ecology of rare intertidal invertebrates to understand their ecological functions and aid their conservation. An example is chitons which are specialists of under-boulder habitat. Little is known about their interactions with the environment or other species, including spirorbid tubeworms which can co-occur in great abundances. This study describes for the first time a distinct pattern of spirorbid-tube fouling across the surfaces of chiton shells, and a similar pattern involving black staining of chitons from anoxic conditions. Posterior valves had 2–5 times as much fouling compared to anterior valves. This may have been caused by forward movement of chitons abrading away the anterior fouling. But signs of wear on shells that are caused by abrasion were also measured, and these were homogenous across the shell surface, suggesting abrasion does not cause the fouling pattern. I found five individuals of Cryptoplax striata (Lamarck, 1819) which were stained black by anoxic iron monosulphides, and the stained area was more than 10 times greater on posteriors than anteriors. These patterns may provide clues about interactions of chitons with fouling species, or about the types of microhabitats where chitons predominantly position different parts of their bodies.